2014
DOI: 10.5194/hess-18-5271-2014
|View full text |Cite
|
Sign up to set email alerts
|

Tracer-based analysis of spatial and temporal variations of water sources in a glacierized catchment

Abstract: Abstract. Snow-dominated and glacierized catchments are important sources of fresh water for biological communities and for populations living in mountain valleys. Gaining a better understanding of the runoff origin and of the hydrological interactions between meltwater, streamflow and groundwater is critical for natural risk assessment and mitigation as well as for effective water resource management in mountain regions. This study is based on the use of stable isotopes of water and electrical conductivity as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 62 publications
13
79
0
Order By: Relevance
“…The trend in isotopic depletion and geochemical enrichment in 2013 is in good agreement with spring monitoring since 2011 [38]. While isotopic depletion until August 2013 indicated increasing snowmelt contributions, isotopic enrichment revealed decreased snowmelt contributions in September.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The trend in isotopic depletion and geochemical enrichment in 2013 is in good agreement with spring monitoring since 2011 [38]. While isotopic depletion until August 2013 indicated increasing snowmelt contributions, isotopic enrichment revealed decreased snowmelt contributions in September.…”
Section: Discussionsupporting
confidence: 67%
“…However, isotopic variations at SPR4 suggested the maximum contribution of snowmelt in June, with a gradual decrease over the season. In contrast, the EC concentration showed gradually increasing concentrations, instead of following isotopic behavior that had occurred during the previous years [38]. Therefore, the highest dilution with snowmelt water containing less solutes was anticipated, and already took place in June.…”
Section: Discussionmentioning
confidence: 97%
“…Snowmelt is a major contributor to streamflow during the spring freshet period in alpine regions and large amounts of snowmelt water infiltrate into the soil and recharge groundwater (Penna et al, 2014). The hydrological response of the stream followed the variations of air temperature, as already observed by Braithwaite and Olesen (1989) (Fig.…”
Section: Temporal Variation In Streamflow During the Melting Seasonmentioning
confidence: 56%
“…Penna et al (2014) showed a preliminary analysis on the highly complex EC and isotopic signature of different waters sampled in the catchment, identifying distinct tracer signals in snowmelt and glacier melt. These two end-members dominated the streamflow throughout the late spring and summer, whereas liquid precipitation played a secondary role, limited to rare intense rainfall events.…”
Section: Penna Et Al: Meltwater Dynamics and Streamflow Responsementioning
confidence: 99%